Estimate of Power Output from Hydraulic Jumps Generated Downstream from Barrages - Sherine Ahmed El-Baradei; Mostafa El-Abd; Nahla Hazem (Journal of Human, Earth, and Future, 2024)
Hydropower is an affordable, sustainable way to generate electricity. Research on hydraulic jumps focuses only on determining head loss across the jump, but there are no studies on generating power from the jump. This research aims to utilize energy dissipated from hydraulic jumps for power-generating purposes and further use this power in real-life applications. This research simulates ideal hydraulic conditions to identify the most stable hydraulic jumps, which will be used to generate power. The Seriakos barrage in Egypt was taken as a case study to simulate energy dissipated/power generated from hydraulic jumps generated downstream. This power is then used to simulate lighting up some streets in Egypt according to Egyptian power consumption standards. An Excel spreadsheet was used to mathematically model generated hydraulic jump types, energy dissipated, and generated power. The study found that submerged flow generates maximum power values from hydraulic jumps as opposed to free flow. The research concluded that energy produced by hydraulic jumps at the Seriakos barrage could light up 78 street light bulbs. Although this is a small amount of power, Egypt could meet a significant portion of its energy needs if hydraulic jumps from all its hydraulic structures were utilized for power generation.